Potent inhibition of human organic cation transporter 2 (hOCT2) by β-carboline alkaloids. (2nd December 2017) - Wagner, David J.; Duan, Haichuan; Chapron, Alenka; Lee, Richard W.; Wang, Joanne
Abstract: 1. Beta-carbolines are indole alkaloids with a wide range of pharmacological and toxicological activities. Beta-carbolines are structurally related to the neurotoxin 1-methyl-4-phenylpyridinium (MPP+), a known substrate of organic cation transporters (OCTs). The goal of this study is to determine the interaction of β-carbolines with human OCT1, 2, and 3 (SLC22A1-3). 2. Dose-dependent inhibition studies were performed for five commercially available β-carbolines using a fluorescent substrate assay in HEK293 cells stably expressing hOCT1-3. The substrate potential was evaluated by uptake assays and the impact of active transport on cellular toxicity examined. 3. All tested β-carbolines potently inhibited hOCT2 with IC50 values in the sub- or low micromolar range. Harmaline is the most potent hOCT2 inhibitor (IC50 = 0.50 ± 0.08 μM). hOCT1 and hOCT3 are less sensitive to β-carboline inhibition. Harmaline, norharmanium, and 2, 9-dimethyl-4, 9-dihydro-3 H -β-carbolinium accumulated 2- to 7-fold higher in cells expressing hOCT1-3. HEK293 cells expressing hOCT1-3 were 6.5- to 13-fold more sensitive to harmane and norharmanium toxicity. 4. Our data support a significant role of hOCT1-3 in tissue uptake and disposition of β-carbolines. Importantly, the potent inhibition of hOCT2 by β-carbolines also raises the concern of potential drug interactions between naturally occurring bioactive alkaloids and drugs eliminated by hOCT2.